Material flow design and simulation for a glass panel recycling installation. Issue 7 (July 2018) - Popa, Cicerone Laurentiu; Cotet, Costel Emil; Popescu, Diana; Solea, Mihai Florin; Şaşcîm (Dumitrescu), Simona Gheorghiţa; Dobrescu, Tiberiu
The current paper presents the design of a glass panels recycling flow and the method used for establishing the optimal processing installation architecture. In the solution provided in the current research, a novel approach centred on applying digital twinning in the design of the requested processing architecture is presented. It involves designing the virtual prototype of the diffused processing architecture and modelling the glass waste flow as a hybrid material flow. Dedicated analysis and simulation software is then used for establishing installation architecture and the specific parameters for each processing and transport capacity. The assessment of different processing scenarios by virtual modelling and simulations can also be used for exploring options to increase productivity and profit for other different recycling architectures. The main practical value of the study consists of creating the means to improve the waste recycling of automotive windshields, float glass or construction glass panels with metallic meshes, all representing categories of waste insufficiently recycled in Romania. The simulation results of the study were validated by tests made on the glass panel recycling installation. Also, a recovery glass rate of minimum 85% of the amount of waste loaded into the recycling system was achieved, obtaining a waste recycling quantity three times higher than initially anticipated.